Cover Feature: N‐Doped Carbon Nanofibrous Network Derived from Bacterial Cellulose for the Loading of Pt Nanoparticles for Methanol Oxidation Reaction (Chem. Eur. J. 8/2018). Issue 8 (27th December 2017) - Yuan, Fanshu; Huang, Yang; Fan, Mengmeng; Chen, Chuntao; Qian, Jieshu; Hao, Qingli; Yang, Jiazhi; Sun, Dongping
Abstract : A three‐dimensional N‐doped carbon nanofibrous network was prepared by annealing a gel containing two inexpensive and ecofriendly precursors, that is, bacterial cellulose and urea, for the loading of Pt nanoparticles. The N doping and higher annealing temperature effectively improved the electron conductivity and provided more active sites for the loading of ultrafine Pt nanoparticles with narrow size distribution. The best catalyst exhibited a remarkably high electrocatalytic activity, excellent poison tolerance and high durability for methanol oxidation reaction. More information can be found in the Full Paper by J. Qian, D. Sun et al. onpage 1844 .